EFFECT OF IODINE DOSES ON HEMATOLOGICAL AND ENZYMES PARAMETERS OF BLACK GOATS DURING LATE PREGNANCY PERIOD - SALIH , HARBI S.; ZEBARI, HAWAR M. H. (Journal of Duhok University, 2022)
The aim of the present study was to evaluate the effect of Iodine supplementation in drinking water on blood hematology and enzyme parameters in Black goats during late pregnancy. Twenty-four pregnant local black goats were used in the present study. Each goat’s was drenched with potassium iodide with 0 mg I/day (control; C), 0.50 mg I/day (treatment one; T1) as low iodine group and 1.00 mg I/day (treatment two; T2) as high iodine group. Blood samples were collected weekly from six weeks before parturition from goats and 1st week of ages of kids. Blood samples were analyzed for hematology and enzymes parameter. Hematological parameters of goats include RBC (106/µL), WBC (103/µL), HB (g/dL), PLT (103/µL), HCT (%), GRA (103/µL), Lymph (103/µL; P=0.005) and MCV were significantly affected by I drenching. There was also a significant effect of I drench on enzyme parameters; alanine transaminase (ALT), alkaline phosphatase (ALP), aspartate transaminase (AST) and creatinine kinase (CK) of goats. In conclusions, I drenching had an impact on the most of the blood hematology and enzymes parameter of the goat throughout the time of the study